2020
DOI: 10.4236/gep.2020.89010
|View full text |Cite
|
Sign up to set email alerts
|

Response of Seasonal Vegetation Dynamics to Climatic Constraints in Northeastern Burundi

Abstract: The climate crises in East Africa (EA), particularly in Burundi, have affected vegetation which, in turn, plays a key role in the climate system by modifying the terrestrial water and energy balance. Consequently, it is vital to understand vegetation dynamics and its response to current and projected climate conditions to support the design of climate resilient land management strategies. The objective of this study was to study the dynamics of vegetation cover over the Northeastern Burundi (NEB) in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Eludoyin et al [46] and Uzoh [47] described wet and dry seasons of Nigeria in such that the rainy (wet) season occur from April to October with moderate rainfall of 1500 to 2000 mm and average temperature of 28 0 C. Results from this study showed that plant thrived well during rainy season across the land uses compared to the dry season that is characterized by high temperature (average of 30 0 C) with little or no rainfall. Dry season last for 4-5 months in the rainforest belt of Nigeria.…”
Section: Effect Of Land Use and Season On Vegetation Indicesmentioning
confidence: 61%
“…Eludoyin et al [46] and Uzoh [47] described wet and dry seasons of Nigeria in such that the rainy (wet) season occur from April to October with moderate rainfall of 1500 to 2000 mm and average temperature of 28 0 C. Results from this study showed that plant thrived well during rainy season across the land uses compared to the dry season that is characterized by high temperature (average of 30 0 C) with little or no rainfall. Dry season last for 4-5 months in the rainforest belt of Nigeria.…”
Section: Effect Of Land Use and Season On Vegetation Indicesmentioning
confidence: 61%
“…As a result of years of monitoring, showed that the decrease in vegetation area was also related to the decrease in water content in the area. This, in turn, means that changes in vegetation dynamics are related to changes in the environment [10,[17][18][19][20]. Results of the use of NDVI indices in determining the area covered by vegetation found that the use of this index in quantitative indicators was effective [13].…”
Section: Resultsmentioning
confidence: 99%
“…The NDVI, which is produced from satellite data, is frequently used to examine the conditions under which live, green vegetation grows and to show how vegetation dynamics respond to climate change [10]. By measuring the relative growth and health of the crop, remote sensing vegetation indices can be used to measure growth in agricultural variability [11].…”
Section: Introductionmentioning
confidence: 99%
“…The Inter-Tropical Convergence Zone (ITCZ) crosses Burundi twice a year and is a major factor in determining precipitation seasonality [30]. Similar to the entire country of Burundi, the northern part of Burundi is normally characterized by four distinct seasons classified into A, B, C, and D seasons [31]. Season A runs for four months: September, October, November, and December (SOND), widely known as the short rain season.…”
Section: The Study Area's Description and Datasetsmentioning
confidence: 99%